2022
DOI: 10.1039/d1dt03658k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural and photophysical properties of dimethylphosphino(perfluoro-)phenylene-based gold(i) dimers

Abstract: Starting with 1,2 dibromobenzene and 1,2,3,4 tetrafluorobenzene, dimethyl(2-(trimethylstannyl)phenyl)phosphane, Me2P(o-C6H4)SnMe2, and dimethyl-[2,3,4,5-tetrafluoro 6 (trimethylstannyl)phenyl]phosphane, Me3P(o-C6F4)SnMe3, were synthesized and used in tin-gold exchange reactions to prepare two gold(I) dimers, bis[(2 dimethylphosphino)phenyl]di-gold(I), [Au2(μ2-C6H4PMe2)2],...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…All NMR spectroscopic data were in good agreement with those previously reported [18] . We recently published the synthesis of dimethyl(2,3,4,5‐tetrafluorophenyl)phosphane ( 2 ) [11] . Phosphanes 1 and 2 were used to generate the copper(I) and silver(I) chloride complexes 3 and 4 in tetrahydrofuran by reaction with the respective metal(I) chlorides.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…All NMR spectroscopic data were in good agreement with those previously reported [18] . We recently published the synthesis of dimethyl(2,3,4,5‐tetrafluorophenyl)phosphane ( 2 ) [11] . Phosphanes 1 and 2 were used to generate the copper(I) and silver(I) chloride complexes 3 and 4 in tetrahydrofuran by reaction with the respective metal(I) chlorides.…”
Section: Resultssupporting
confidence: 86%
“…[18] We recently published the synthesis of dimethyl(2,3,4,5-tet-rafluorophenyl)phosphane (2). [11] Phosphanes 1 and 2 were used to generate the copper(I) and silver(I) chloride complexes 3 and 4 in tetrahydrofuran by reaction with the respective metal(I) chlorides. In each case, the isolated complex always contained a ratio of two phosphanes to one metal chloride units, regardless of the employed equivalence ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that the fluorination has no major impact on the intramolecular Au⋅⋅⋅Au interaction distance, but strongly predetermines the intermolecular aggregation in the solid‐state. The hydrogen substituted gold(I) dimer aggregates chainlike with intermolecular Au⋅⋅⋅Au contacts, while the fluorine substituted gold(I) dimer shows no additional intermolecular Au⋅⋅⋅Au contacts, but stacking interactions between the perfluorophenylene groups [8] …”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen substituted gold(I) dimer aggregates chainlike with intermolecular Au•••Au contacts, while the fluorine substituted gold(I) dimer shows no additional intermolecular Au•••Au contacts, but stacking interactions between the perfluorophenylene groups. [8] In this work we wanted to investigate the phenyl-and mesitylphosphane-substituted gold(I) dimers based on the 3,3,4,4,5,5-hexafluorocyclopentene framework, [F 6 cyp(PR 2 )Au] 2 (R = Ph, Mes), and their precursor molecules regarding the different steric demand of the phosphane donor function and the effect on the solid-state structures. The hexafluorocyclopentene (F 6 cyp) framework was used to avoid additional intermolecular aryl-aryl stacking interactions between the ligands like in the case of [Au 2 (μ-2-C 6 F 4 PMe 2 ) 2 ].…”
Section: Introductionmentioning
confidence: 99%